THE EVALUATION OF MINIMUM SERVICE STANDARD AND PASSANGER SATISFACTION LEVEL ON JEMBER RAILWAY STATION THROUGH BOARDING PASS SYSTEM IMPLEMENTATION: Evaluasi Standar Pelayanan Minimum dan Tingkat Kepuasan Penumpang di Stasiun Kereta Api Jember dengan Penerapan Sistem Boarding Pass - Ratnasari, Septiana Desy; Kriswardhana, Willy; Hayati, Nunung Nuring (Universitas Jember, 2017)
In fullfiling the needs of public transportation in Jember District, many people demand a safe, fast, economical and fluently transportation. The railway is more efficient public transportation because it is more economical, safe and travel time is fast. Therefore PT. Kereta Api Indonesia (Persero) needs to improve the service and facilities of Jember Station in order to become the main attraction of people to use rail transport services. The implementation of the Boarding Pass system in Jember Station currently needs to be evaluated to assess station services and facilities based on Regulation of the Minister of Transportation Number: PM 48 Year 2015. Analysis of minimum service standards in Jember Station has been done before applying the boarding pass system. This study also aims to determine the satisfaction and expectations of passengers as measured by the questionnaire. The questionnaire data using Likert scale was processed using SPSS program with Importance Performance Analysis (IPA) method and described with Cartesian diagram. The gap between the level of satisfaction and interest is obtained in the form of gap value with the largest indicator below the average that is the problem of parking space available at Jember Station. Dalam memenuhi kebutuhan transportasi massal di Kabupaten Jember, banyak masyarakat menuntut suatu angkutan umum yang aman, cepat, ekonomis dan lancar. Kereta api merupakan transportasi massal yang cukup efisien karena lebih ekonomis, aman dan waktu tempuh yang cepat. Maka dari itu PT. Kereta Api Indonesia (Persero) perlu meningkatkan pelayanan dan fasilitas Stasiun Jember agar menjadi daya tarik masyarakat untuk menggunakan jasa angkutan kereta api. Penerapan sistem Boarding Pass di Stasiun Jember saat ini perlu dievaluasi untuk menilai pelayanan dan fasilitas stasiun berdasarkan Peraturan Menteri Perhubungan Nomor: PM 48 Tahun 2015. Analisa standar pelayanan minimum di Stasiun Jember sudah pernah dilakukan sebelum penerapan sistem boarding pass. Penelitian ini juga bertujuan untuk mengetahui kepuasan dan harapan penumpang yang diukur berdasarkan kuesioner. Data kuesioner menggunakan skala Likert diolah menggunakan program SPSS dengan metode Importance Performance Analysis (IPA) dan digambarkan dengan diagram Kartesius. Kesenjangan antara tingkat kepuasan dan kepentingan didapat berupa nilai GAP dengan indikator terbesar di bawah rata-rata yaitu permasalahan lahan parkir yang tersedia di Stasiun Jember.